Model of Zakat Utilization in the Covid-19 Pandemic Era: Perspective of Maqashid Sharia - Ramadhita, Ramadhita; Sudirman, Sudirman; Bachri, Syabbul (AL-ISTINBATH : Jurnal Hukum Islam, 2022)
The Covid-19 pandemic brought significant changes in human social life. One of the most affected sectors is the economy. One of the financial institutions that can be used to alleviate poverty is zakat. This article aims to describe the utilization of zakat in East Java province and analyze it using the principles of Maqashid Sharia. This article is based on empirical research using a conceptual approach. Primary data was generated from interviews with Badan Amil Zakat East Java, Yayasan Dana Sosial Al-Falah Malang, Nurul Hayat Malang, and Baitul Mal Hidayatullah Malang. This study shows that zakat management institutions have distributed productive zakat. There are three models of the productive distribution of zakat: the provision of Business Capital, Revolving Funds, and scholarships. Productive management of zakat can be maximized through mentoring and monitoring the program. Assistance to mustahiq beneficiaries can improve the quality of religious knowledge, reason, and economic income as stated in maqashid syariah.